Thrive in a Digital Age: Understanding ICT-enabled Work Experiences through the Lens of Work Design - Wang, Bin (Curtin University, 2020)
As information communication technology (ICT) becomes ever more embedded in today’s organizations, the nature of employees’ jobs and work experiences are being strongly affected by ICT usage at work. Based on the work design perspective, I conducted three studies to understand the intertwined relationships among technology, human beings, and work. This thesis helps to deepen our understanding on ICT-enabled work experiences, to stimulate the development of work design theories in the digital era, and guide contemporary managerial practices.